The field guide to early man - Lambert, David (New York, N.Y. : Facts on File, 1987)
An illustrated introduction to the evolution of man, from the early hominids to the present day.
Includes index.
Keywords: Human evolution; Prehistoric peoples; Human beings; Evolution; Prehistoric peoples